Workforce needs in the fashion industry: Relevance to the vocational fashion design curriculum - Annisau Nafiah; R. Machmud Sugandi; Hariani Aprilia; Wulidah Ning Tiasari; Arasinah Binti Kamis; Asliza Aris (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2025)
The rapid transformation of the fashion industry due to digitalization and globalization has significantly reshaped the competencies required of its workforce. This study aims to reveal the essential skills demanded by fashion industry stakeholders, assess the relevance of the fashion design vocational curriculum to these industry needs, and examine the correlation between educational content and industry expectations. Using a quantitative approach with survey and document analysis, data were collected from 96 respondents, comprising fashion industry practitioners, vocational teachers, and alumni. The findings indicate that the industry prioritizes a hybrid competency set comprising advanced technical skills, digital fluency (e.g., computer-aided design and 3D fashion design software), soft skills, and entrepreneurial acumen. However, the current vocational curriculum remains moderately relevant (mean = 3.88), with significant gaps in the integration of digital and entrepreneurship. Pearson correlation analysis reveals a very strong and statistically significant relationship (r = 0.952, p < 0.01) between curriculum content and industry expectations. These results underscore the urgency of adopting a demand-driven, digitally oriented, and industry-partnered curriculum reform. The study offers valuable insights for policymakers, educators, and curriculum developers seeking to enhance graduate employability and align vocational education with the evolving dynamics of the fashion sector.